Determining immunisation status of children from history: a diagnostic accuracy study - Nohavicka, L; Ashdown, H; Kelly, D (BMJ Publishing Group, 2013)
OBJECTIVES: Children presenting unplanned to healthcare services are routinely asked about previous immunisations as part of their assessment. We aimed to assess the accuracy of screening children for immunisation status by history. DESIGN: Diagnostic accuracy study. We compared information from patient history by a retrospective review of notes and used a central database of child immunisation records as the reference standard. SETTING: Paediatric emergency department in a tertiary hospital in Oxford, UK. PARTICIPANTS: Consecutive children aged 6 months to 6 years presenting over a 2-month period. OUTCOME MEASURES: Proportion of children with documented immunisation history; sensitivity and specificity of detecting overdue immunisations by history compared to central records. RESULTS: 1166 notes were surveyed. 76.3% children were asked about immunisations. The proportion of children who were fully immunised on central records was 93.1%. History had a sensitivity of 41.3% (95% CI 27% to 56.8%) and a specificity of 98.7% (95% CI 97.5% to 99.4%) for detecting those who were overdue. Negative predictive value was 95.8% (95% CI 93.9% to 97.2%). Only around a third of children with overdue immunisations are detected by the current screening methods, and approximately 1 in 20 children stated as being up to date are in fact overdue. CONCLUSIONS: History had poor sensitivity for identifying overdue immunisation. Strategies to improve detection of children overdue with immunisation should focus on alternative strategies for alerting clinicians, such as linkage of community and hospital electronic records.